Cover Feature: Tuning of the Self‐Threading of Ring‐in‐Ring Structures in Aqueous Media (Chem. Eur. J. 65/2019). Issue 65 (9th October 2019) - Neira, Iago; Alvariño, Cristina; Domarco, Olaya; Blanco, Víctor; Peinador, Carlos; García, Marcos D.; Quintela, José M.
Abstract : The influence of the hydrophobic core on the equilibrium between a series of Pd II /Pt II ‐directed self‐assembled metallacyles with their ring‐in‐ring complexes is reported in this work. It was possible to fine‐tune the system response against external stimuli such as concentration, temperature (illustrated in the cover), polarity or addition of an aromatic guest. More information can be found in the Full Paper by V. Blanco, C. Peinador, M. D. García, et al. on page 14834 .